THE INFLUENCE OF BUREAUCRATIC PATHOLOGY ON EMPLOYEE PERFORMANCE IN E-KTP SERVERS IN THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF BANDUNG CITY - Aswin Palls (Universitas Pasundan, 2020)
The pathology of the bureaucracy is a disease in the state bureaucracy that arises due to the behaviour of the bureaucrats and the conditions that open up opportunities for it, whether related to politics, economics, social culture and technology. The role of the bureaucracy as the implementer of political policy, or in other words the bureaucracy as the organizer of the government, then the pathology of the bureaucracy can be interpreted as a problem or problem that occurs in government administration due to the inability of the bureaucracy's performance to meet public needs properly. The pathology of the bureaucracy can be manifested in the inability of political officials in the executive (elected due to political mandates) or the performance problems of elected public officials, namely officials in the bureaucracy who occupy positions due to the political process. Or because of the performance of administrative leaders, namely career bureaucrats who occupy career positions in the bureaucracy. Or the bureaucracy itself as an institution, or government agents or bureaucrats who are unable to provide public satisfaction. With the emergence of bureaucratic disease in the organizational structure, it has become a major influence in service. In addition, there is still discrimination in services or differences in services including the E-KTP making service provided by officers to the community. The level of response or staff skills which is still low, needs to be improved and is important in influencing the level of community satisfaction where the service is fair and regardless of status and position supported by the availability of adequate facilities and infrastructure in administrative services.